(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
This review explores some aspects of Acetes spp., which covers its morphological and molecular identification and geographical distribution. Identification methods, including morphological and molecular approaches, are presented to improve the understanding of Acetes spp. diversity. The review explores the global distribution of each species of Acetes. The information presented serves as a foundational resource for researchers, practitioners, and enthusiasts interested in the various aspects of Acetes spp.